Alzheimer’s Disease Genetics: From the Bench to the Clinic - Karch, Celeste M.; Cruchaga, Carlos; Goate, Alison M. (Neuron (Cambridge, Mass.), 2014)
Alzheimer’s disease (AD) is a clinically heterogeneous neurodegenerative disease with a strong genetic component. Several genes have been associated with AD risk for nearly 20 years. However, it was not until the recent technological advances that allow for the analysis of millions of polymorphisms in thousands of subjects that we have been able to advance our understanding of the genetic complexity of AD susceptibility. Genome-wide association studies and whole-exome and whole-genome sequencing have revealed more than 20 loci associated with AD risk. These studies have provided insights into the molecular pathways that are altered in AD pathogenesis, which have, in turn, provided insight into novel therapeutic targets. Karch et al. discuss how the recent technological advances in human genetics have led to an increased understanding of the genetic architecture and molecular pathways involved in Alzheimer’s disease.